(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis explores the interplay between business negotiations and digital tools within the context of cross-cultural communication. It highlights the challenges posed by cultural differences in negotiation processes and the potential of digital technologies to bridge these gaps. By analyzing materials in both English and Uzbek, the study aims to identify effective strategies for successful negotiations in a globalized environment. The research emphasizes the importance of understanding cultural nuances and leveraging digital platforms to enhance communication and collaboration among diverse stakeholders.